Comparison of local excision and total mesorectal excision for rectal cancer: Systematic review and meta-analysis of randomised controlled trial - Zan Meng; Zehong Liu (Heliyon, 2024)
Objectives: To report the first and largest systematic review and meta-analysis of radomised controlled trials (RCTs) to compare the efficacy and safety of transanal endoscopic microsurgery (TEM) and total mesorectal excision (TME) for rectal cancer for perioperative and oncological outcomes. Methods: We conducted a systematic literature retrieval via PubMed, Embase, Web of Science, and Cochrane until December 2022 for RCTs which evaluated the efficacy and/or safety between TEM and TME for rectal cancer. Outcomes included operative time, blood loss, transfusion rates, hospital stay, complication rates, recurrence rates, and mortality. Results: A total of 5 RCTs involving 545 patients (272 TEM versus 273 TME) were included for the meta-analysis. There were no significant differences between the two groups for age, gender, and distance from lower border of tumor to anal verge. Meta-analysis found that the TEM group was significantly favorable than the TME group for blood loss (WMD: 172.01; 95 % CI: 212.78, −131.24; P < 0.00001), hospital stay (WMD: 2.58; 95 % CI: 3.01, −2.16; P < 0.00001), operative time (WMD: 81.86; 95 % CI: 87.51, −76.21; P < 0.00001) and transfusion rates (RR: 0.05; 95 % CI: 0.01, 0.38; P = 0.004). The complication rates (RR: 0.60; 95 % CI: 0.32, 1.11; P = 0.10), recurrence rates (RR: 1.10; 95 % CI: 0.66, 1.83; P = 0.72), and mortality (RR: 1.23; 95 % CI: 0.67, 2.26; P = 0.51) were similar in the two groups. Conclusions: TEM was an effective and safe approach with advantages in perioperative outcomes compared with TME approach. Caution should be exercised in interpreting the differences in surgical complications between TEM and TME group due to significant heterogeneity and instability.